Public procurement and tax havens - Petr Janský; Miroslav Palanskỳ; Jiří Skuhrovec (Charles University in Prague, Institute of Economic Studies (IES), 2023)
To understand public procurement suppliers linked to tax havens, we analyse datasets of tender-level public procurement and firm-level suppliers a provide a series of stylized facts. We estimate that around 5% of tenders by value (145 billion EUR yearly) are supplied by firms with ownership links to tax havens that are black-or grey-listed by the EU. For example, firms linked to the British Virgin Islands and Bermuda supply tenders worth over 900 per cent of their GDP. To address the question of which tenders are more likely to be supplied by firms linked to tax havens, we draw on a theoretical model and a tender-level empirical analysis. We find that tenders co-financed from EU funds and those attracting a larger number of bidders are less likely to be supplied by firms linked to tax havens. Any policy intervention might therefore rely on both an increased government oversight associated with EU funds or an increased firm competition.
Keywords: F36; F65; G28; H87; H57; 330; public procurement; government expenditures; offshore finance; secrecyjurisdictions; tax havens